Openness and the Degree of Impact on Engagement Learner Department of Architecture Case Study - Asmaa M.H Al-Muqaram, Ass. Prof. Dr.; Riyam Rajab Fanjan Al-Amara, Lecturer (Journal of Engineering, 2017)
This paper concerns with openness concept in contemporary learning environment, which ranges from physical characters to its relation with learning efficiency and its output. Previous literatures differ to clear the effect of openness on the engagement between learner within themselves, and with this kind of spaces. Engagement means: active participation, the ability of making dialogue, self-reflection and the ability to explore and communicate with them and within learning space. Research roblem was: The lack of knowledge about the effect of Openness on learner engagement with learning spaces. The two concepts were applied on three types of learning spaces in the Department of the Architecture in the University of Technology, according to their measurements. The research found that there are two types of engagment, positive and negative, that effect of openness in learning space, as increasing of the openness in learning space as more of the positive engagement of the learner, offset by a decrease in the negative engagement which cause conditions of the boredom and loss of concentration and scattering the learner mind - within this kind of space.